Penentuan Kualitas Biji Kopi Pada Koperasi Solok Radjo Menggunakan Metode TOPSIS Fuzzy MADM - Hurriyah, Salsa Sabitha; Subhan, Muhammad (Journal of Mathematics UNP, 2023)
To determine the quality of coffee beans, expertis and accuracy are needed to make the right decision, so there are no mistakes in labeling the qualityof coffee beans which can cause losses. This research aims to assist in determining the quality of coffee beans using the TOPSIS Fuzzy MADM method with four criteria, namely: water content, defects, scent, and ground height of the coffee beans. Criteria assessments are determined subjectively and objectively. The weight values of the criteria are obtained subjectively based on expert opinions and objectively obtained using the TOPSIS method. The results of this research is preference value ranking of all alternatives. The results of the accuracy test comparing the analysis results from experts with the TOPSIS Fuzzy MADM method obtained an accuracy rate of 85%, classified as good criteria that can be used todetermine the quality of coffee beans precisely and well.